Safety Culture Awareness Of Laboratory Activities Among Universiti Sains Malaysia (USM) Engineering Students - Salleh, Siti Norfatihah (Universiti Sains Malaysia, 2022)
In Malaysia, where serious problems with worker safety and health are a result of workplace negligence, which can occasionally result in tragic accidents, occupational safety and health administration is an essential part of human resource management. To avoid losing skilled workers, controlling occupational safety and health should be given top priority in every plant and organization. The university level needs to increase safety awareness of students through learning procedures and instructional strategies. This study aims to study evaluate the level of safety awareness among undergraduates. A survey was done with 80 USM engineering students using questionnaires that are divided into a few sections: A. OSH Policy, B. Personnel Protective Equipment (PPE), C. Mechanical Safety, D. Tool Safety, E. 5S Practice, and F. Hazard and Risk Prevention. Then, the questionnaires that were fully answered by the respondents were analysed using Excel with the descriptive analysis method in the results. The results show that the safety awareness in laboratory of second year students is lower than the other batch. In conclusion, the future study that can be done are increasing the awareness on safety culture in laboratory of the students for different courses and year of study.